SYNERGY OF DIGITAL LOGISTICS AND DIGITAL MARKETING INTEGRATION - BLAHUN, Ivan; ANDRUSHKEVYCH, Zinayida; BOIKO, Ruslan (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article highlights the relevance of integrating digital logistics and digital marketing as a key factor in improving the efficiency of business processes in the current conditions of digital transformation. The article considers the importance of using digital tools in the marketing and logistics activities of enterprises, in particular, technologies such as artificial intelligence (AI), Internet of Things (IoT), blockchain, big data analytics, CRM systems, cloud services, SEO, TMS, WMS, and others. It is emphasized that the integration of these tools allows to optimize supply chains, personalize customer interaction, reduce costs and increase efficiency.Attention is focused on the synergistic effect of integration, which ensures an increase in the competitiveness of enterprises by improving customer experience, reducing costs and adapting to changes in the market environment. The author outlines the key performance indicators of integration, including reduction of delivery time, reduction of logistics costs, increase of customer loyalty and business adaptability to market challenges.It is determined that the integration of digital tools allows enterprises to ensure transparency of supply chains, automation of logistics and marketing processes, while increasing business flexibility and sustainability. The article provides practical recommendations for creating integrated platforms, introducing innovative technologies and developing digital competencies of personnel, which contributes to the formation of competitive advantages of enterprises in the modern globalized environment.It is concluded that the integration of digital marketing and logistics is a strategic direction for the development of enterprises, which ensures their sustainability, adaptability and compliance with modern market challenges. Prospects for further research include studying the impact of digital technologies on sustainable business development, creating integrated platforms, and adapting business models to modern conditions.
Keywords: digital marketing; digital logistics; synergistic effect; digital tools; key performance indicators; customer experience